Alterations of the neutrophil–lymphocyte ratio during the period of stable and acute exacerbation of chronic obstructive pulmonary disease patients. (6th August 2015) - Taylan, Mahsuk; Demir, Melike; Kaya, Halide; Selimoglu Sen, Hadice; Abakay, Ozlem; Carkanat, Ali İhsan and Abakay, Abdurrrahman and Tanrikulu, Abdullah Cetin and Sezgi, Cengizhan
Abstract: Objectives: We aimed to investigate the importance of neutrophil–lymphocyte ratio (NLR) in patients with chronic obstructive pulmonary disease (COPD) for identifying the severity of inflammation and recognition of acute exacerbation. Methods: We retrospectively enrolled 100 patients with a diagnosis of COPD exacerbation who were admitted to our clinic. Complete blood count (CBC), measurement of C reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were determined within 2 h of hospital admission. Three months after an acute exacerbation, these measurements were obtained from the same patients during the stable period of COPD. The control group included 80 healthy subjects. NLR was calculated from CBC. Results: NLR and other inflammatory markers, such as WBC, CRP and ESR were found to be significantly elevated in exacerbated COPD compared to stable COPD and control participants. There was a significant correlation of NLR with CRP ( r = 0.415, P < 0.001), WBC ( r = 0.304, P = 0.002) and ESR ( r = 0.275, P = 0.035). For an NLR cutoff of 3.29, sensitivity for detecting exacerbation of COPD was 80.8% and specificity was 77.7% (AUC 0.894, P = 0.001). Some patients presenting with acute exacerbation of COPD and CRP, WBC or ESR levels lower than the optimal cut‐off value had high NLR values. Conclusions: Elevated NLR can be used as a marker similar to CRP, WBC and ESR, in the determination of increased inflammation in acutely exacerbated COPD. NLR could be beneficial for the early detection of potential acute exacerbations in patients with COPD who have normal levels of traditional markers.